The Meaning of Istifham in the Qur'ān Juz 26 (Balāghah Study) - Nur Fadila; Agussalim Beddu Malla; Fihris Khalik (Universitas Muhammadiyah Gorontalo, 2025)
Interrogative sentences in the science of Balāghah (rhetoric) often carry additional meanings. This study aims to uncover the meanings of question sentences in the Qur'ān, Juz 26, from the perspective of Balāghah (rhetoric). This library research (literature review) with a qualitative descriptive approach is intended to systematically, factually, scientifically, analytically, and accurately describe facts using a contextual approach and tafsir (interpretation) approach. The results of this study indicate that the rhetorical meanings found within include: the meaning of at-tawbīkh (rebuke or admonition), which appears in 3 verses; the meaning of an-nafī (negation), found in 1 verse; the meaning of attaqrīr (affirmation), in 1 verse; the meaning of al-inkār (denial), in 16 verses; the meaning of al-istihzā' (mockery), in 1 verse; the meaning of at-tahwīl (intimidation or frightening), in 2 verses; the meaning of al-istib’ād (exclusion), in 1 verse; and the meaning of at-tafkhīm (emphasis or intensification), in 1 verse.